Logo and Packaging Creation Training as a Rebranding Effort for MSMEs to Increase Sales - Riyanti, Menul Teguh; Ariani, Ariani; Jasjfi, Elda Franzia; Novianti, Erlina; Setiadi, Virginia Suryani; Hidayatullah, Ahmad Syarief; Quincy, Quincy (Universitas Lambung Mangkurat, 2025)
The Covid-19 pandemic has impacted the sustainability of Micro, Small, and Medium Enterprise (MSMEs) in Tanjung Duren Village, Grogol District, West Jakarta. Due to the pandemic, several MSMEs suffered losses and were forced to close their businesses. After the pandemic, MSMEs activists began to improve themselves and adjust market developments. One of the strategies to attract market interest is rebranding with an attractive appearance through logos and packaging of MSMEs products. This condition became a concern for the community service team, Faculty of Art and Design (FSRD) Universitas Trisakti, so they provided training on creating logos with the Canva application and packaging design. This training aims to help MSME players rebrand through attractive logos and packaging so that the products sold become the community's choice. This PkM activity applies a mentoring method with a PAR (Participatory Action Research) approach that actively involves participants in implementing activities. A total of 10 (ten) food and beverage MSMEs players, all women, attended the training held on Friday, May 03, 2024, at the RW 007 secretariat office, Tanjung Duren Utara Village, West Jakarta. Through this training, the participants, who are MSME players, gained knowledge in designing attractive logos and product packaging so that they are expected to increase their product sales.